Venous Thromboembolism in Critical Illness and Trauma: Pediatric Perspectives - Chima, Ranjit S.; Hanson, Sheila J. (Frontiers in Pediatrics, 2017)
Abstract Critically ill children and those sustaining severe traumatic injuries are at higher risk for developing venous thromboembolism (VTE) than other hospitalized children. Multiple factors, including the need for central venous catheters, immobility, surgical procedures, malignancy and dysregulated inflammatory state confer this increased risk. As well as being at higher risk of VTE, this population is frequently at increased risk of bleeding, making the decision of prophylactic anticoagulation even more nuanced. The use of pharmacologic and mechanical prophylaxis remains variable in this high-risk cohort. VTE pharmacologic prophylaxis is an accepted practice in adult trauma and intensive care to prevent VTE development and associated morbidity, but is not standardized in critically ill or injured children. Given the lack of pediatric specific guidelines, prevention strategies are variably extrapolated from the successful use of mechanical and pharmacologic prophylaxis in adults, despite the differences in developmental hemostasis and thrombosis risk between children and adults. Whether the burden of VTE can be reduced in the pediatric critically ill or injured population is not known given the lack of robust data. There are no trials in children showing efficacy of mechanical compression devices or prophylactic anticoagulation in reducing the rate of VTE. Risk stratification using clinical factors has been shown to identify those at highest risk for VTE and allows targeted prophylaxis. It remains unproven if such a strategy will mitigate the risk of VTE and its potential sequelae.